2021
DOI: 10.3390/vaccines9040330
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Hesitancy among Young Adults in Saudi Arabia: A Cross-Sectional Web-Based Study

Abstract: Ending the COVID-19 pandemic requires achieving herd immunity, either by previous infection or by vaccination. However, concerns about the COVID-19 vaccine are growing around the globe. The current study was conducted to investigate young the adult population’s hesitancy towards the vaccine. The study used a prospective cross-sectional design. Data was collected using an online self-administered questionnaire. A total of 862 Saudi adults participated. Information was gathered on the participants’ perspectives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
74
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(102 citation statements)
references
References 20 publications
10
74
1
Order By: Relevance
“…Our study also highlighted that public trust on the healthcare system and risk perception toward the virus were the significant predictive behavior in accepting the vaccine, as stated in previous studies ( 20 24 ).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our study also highlighted that public trust on the healthcare system and risk perception toward the virus were the significant predictive behavior in accepting the vaccine, as stated in previous studies ( 20 24 ).…”
Section: Discussionsupporting
confidence: 85%
“…The healthcare workers reported 50.52% willing to have the COVID-19 vaccine in Saudi Arabia ( 21 ). The young adults have a lower acceptability (48.0%) of the vaccine in Saudi Arabia, as reported in a recent study ( 20 ). A study conducted among working people in Hong Kong, China, also reported a lower rate of intention in vaccination between the first wave (44.2%) and the third wave (34.8%) ( 17 ).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Vaccine effectiveness is one of the reasons for vaccine hesitancy among the population. A previous study has reported that 49.9% of their participants agreed that the effectiveness of the vaccine is the reason for their hesitancy [13]. Similarly, in our study, the majority of participants agreed that there is a need for vaccination; yet, safety and efficacy of the vaccine has been the major cause of hesitancy in the general population.…”
Section: Discussionsupporting
confidence: 78%
“…Fifth, consistent with other studies, those who had concerns over COVID-19 vaccines' side-effects and effectiveness were more likely to be vaccine hesitant [26,[28][29][30]. This highlights the prevailing environment where there is heightened concern about the effectiveness and side effects of COVID-19 vaccines.…”
Section: Discussionsupporting
confidence: 78%